The Importance of Promoting the Principles of Good Governance to Achieve Legal Security - Ahmed, Shahla Ali (Journal of Legal and Political Studies, 2025)
Legal security is a fundamental objective pursued by most legislative systems due to its crucial role in ensuring stability and stability in individuals' transactions. It safeguards the consistency of legal relationships and protects individuals from abrupt legislative changes and arbitrary laws that may undermine their trust in the legal system. Achieving legal security necessitates improving the quality of legislation and ensuring its relative stability. However, enacting laws alone does not suffice to guarantee legal security; it requires the active involvement of administrative bodies responsible for law enforcement. These entities must operate efficiently and effectively to establish a legally stable environment for individuals. Administrative bodies wield exceptional privileges and powers in issuing decisions that impact individuals' acquired rights and legal status, whether through amendments, enactments, or revocations. Before issuing or retracting decisions, administrative authorities must exercise restraint, avoid excessive discretionary power, and refrain from making arbitrary or premature rulings. Their decisions must be grounded in legal provisions to prevent destabilization of individuals' legal standing and infringement upon their rights. Even in matters concerning administrative contracts and public financial management, authorities must ensure prudent handling of public funds and actively combat financial and administrative corruption. This can be achieved through strict accountability measures, monitoring mechanisms, and adherence to the principle of transparency. Good governance plays a crucial role in enhancing legal security by applying core administrative principles. The stronger the framework of good governance, the greater the level of legal security attained by individuals. There is an intrinsic relationship between good governance and legal security, both of which have become essential elements in modern societies and states, attracting attention not only at the national level but also on an international scale.. Keywords: Legal security, good governance, Guarantees to achieve legal security , principles of good governance.
Keywords: Legal security; good governance; Guarantees to achieve legal security; principles of good governance